Coping and Protective Behavior of Residents of Radioactive Contaminated Territories Depending on Age and Gender - Borisova, I.V.; Gulakova, E.S. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2018)
The article examines the results of an empirical study of the coping and protective behavior of the residents of radioactive contaminated territories, depending on age and gender. The specifics of coping and protection are revealed depending on age and gender. It is shown that young men and women more often use non-constructive ways of coping behavior to cope with difficult life situations, in comparison with adult men and women. Men are worse than women at relieving stress and maintaining self-esteem in difficult life situations through the use of coping strategies. It was established that the residents of radioactive territories do not want to take responsibility for their lives, but passively expect assistance without any independent actions aimed at resolving their problems. It was revealed that substitution as a mechanism of psychological defense is more pronounced in adolescent and mature men than in girls and women, respectively. The relationship between defensive and coping behavior in adolescence and adulthood was described. It was established that in adolescence, confrontational coping, manifested through aggressive efforts aimed at actively asserting one’s opinion and desires in relations with others and trying to have one’s own way, through chaotic activities that do not change the situation, is closely related to the mechanisms of psychological defense. Substitution does not allow the use of constructive ways of coping both in adolescence and in adulthood. The results of the study can be used to provide psychological assistance to residents of radioactive contaminated areas.